The Impact of Exploratory Practice: A Mixed-Methods Study on Writing Motivation and Performance among EFL Undergraduates - Adara, Reza Anggriyashati; Victorynie, Irnie; Hidayati, Istiqlaliah Nurul; Fitriana, Meida; Tabunan, Mark Louie (FKIP Universitas Lampung, 2025)
The Impact of Exploratory Practice: A Mixed-Methods Study on Writing Motivation and Performance among EFL Undergraduates. Investigating the effects of Exploratory Practice (EP) on English as a Foreign Language (EFL) learners’ motivation and writing skills can provide new insights into improving writing classes. Objective: The objective of the present study is to investigate the impacts of EP on a group of EFL college students’ writing motivation and writing skills. Methods: This study employed a quasi-experimental research design, implementing reflective discussions and collaborative inquiry through EP. To understand improvements in students’ motivation, questionnaires and semi-structured interviews were administered to 23 participants. Findings: The quantitative results showed some improvements in students’ self-efficacy, extrinsic motivation, and writing scores. However, intrinsic motivation and efforts to complete writing tasks did not show statistically significant changes. To better understand these nonsignificant results, qualitative data were used to explore students’ experiences during the EP process. Participants reported increased confidence, reduced anxiety, and greater ability to organize ideas through peer discussions and reflective activities. They also described a more meaningful, less mechanical writing process, which may indicate early signs of motivational internalization, even if not reflected quantitatively. Conclusion: The outcomes imply that EP can be a feasible approach to enhance students’ motivation and writing skills in an EFL context. Despite the apparent success of EP in this study, its successful implementation in writing classrooms depends on students’ involvement in the learning and teaching process and teachers’ continuous support. Keywords: exploratory practice, writing motivation, EFL learners, reflective learning, writing performance.